Oral anticoagulation across diabetic subtypes in patients with newly diagnosed atrial fibrillation: a report from the GARFIELD-AF registry - Bassand, Jean-Pierre; Virdone, Saverio; Camm, A. John; Fox, Keith A. A.; Goldhaber, Samuel Z.; Goto, Shinya; Haas, Sylvia; Hacke, Werner; Kayani, Gloria; Keltai, Matyas; Misselwitz, Frank; Pieper, Karen S.; et al. (Diabetes, obesity and metabolism, 2023)
AIMS: This study aims to describe both management and prognosis of patients with diabetes mellitus (DM) and newly diagnosed atrial fibrillation (AF), overall as well as by antidiabetic treatment, and to assess the influence of oral anticoagulation (OAC) on outcomes by DM status. METHODS: The study population comprised 52 010 newly diagnosed patients with AF, 11 542 DM and 40 468 non-DM, enrolled in the GARFIELD-AF registry. Follow-up was truncated at 2 years after enrolment. Comparative effectiveness of OAC versus no OAC was assessed by DM status using a propensity score overlap weighting scheme and weights were applied to Cox models. RESULTS: Patients with DM [39.3% oral antidiabetic drug (OAD), 13.4% insulin ± OAD, 47.2% on no antidiabetic drug] had higher risk profile, OAC use, and rates of clinical outcomes compared with patients without DM. OAC use was associated in patients without DM and patients with DM with lower risk of all-cause mortality [hazard ratio 0.75 (0.69-0.83), 0.74 (0.64-0.86), respectively] and stroke/systemic embolism (SE) [0.69 (0.58-0.83), 0.70 (0.53-0.93), respectively]. The risk of major bleeding with OAC was similarly increased in patients without DM and those with DM [1.40 (1.14-1.71), 1.37 (0.99-1.89), respectively]. Patients with insulin-requiring DM had a higher risk of all-cause mortality and stroke/SE [1.91 (1.63-2.24)], [1.57 (1.06-2.35), respectively] compared with patients without DM, and experienced significant risk reductions of all-cause mortality and stroke/SE with OAC [0.73 (0.53-0.99); 0.50 (0.26-0.97), respectively]. CONCLUSIONS: In both patients with DM and patients without DM with AF, OAC was associated with lower risk of all-cause mortality and stroke/SE. Patients with insulin-requiring DM derived significant benefit from OAC.